Pendampingan Remaja Melalui Empowering Community Psychology Untuk Meningkatkan Orientasi Masa Depan - Aliza, Novia Fetri (Universitas Muhammadiyah Yogyakarta, 2018)
The purpose of this program is to change the adolescent mindset as well as improve the future orientation of youth in education. Furthermore, the community is expected to have awareness to run its the role as a support system in improving the future orientation of adolescents. The method of implementation of this program is empowering community psychology approach implemented through several stages, namely providing group counseling and motivation to adolescents, counseling to improve the participation of parents and teachers in improving the future orientation of adolescents. Parents tales of psycho education about educating teenagers, the importance of continu-ing adolescent education and improving parental patterns of concern about adolescents who find it difficult to get a mate. To the group of teachers given counseling effective communication with adolescents. The result of this assistance is the emergence of awareness of students (adolescents) to continue education to a higher level such as high school or vocational school by 85% from the previous only 40 %, while those who have motivation to continue education to college increased 10% from 0 %. Teenagers are still worried about getting childrenâ€™s labels unsold by the public, but have started to decrease. Parents begin to have an awareness of the importance of their role in the future of their teenagers. Teachers gain insight and discover new methods of effective communication with adoles-cents.Â Key word: Community Psychology, teens, Future Orientation